Mechanical vibration analysis and computation - Newland, D. E. (Dover books on engineering., 2006)
Focusing on applications rather than rigorous proofs, this volume is suitable as a text for upper-level undergraduates and graduate students concerned with vibration problems. It also serves as a practical handbook for performing vibration calculations and features extensive appendices and answers to selected problems. 128 figures. 1989 edition.